Feasibility of Implementing Mini-Clinical Evaluation Exercise (Mini-CEX) as a Formative Assessment Tool in Postgraduate Surgical Training - Faisal Ghani Siddiqui, Omema Saleem, Mujeeb Ur Rehman Malik, Muhammad Taqi Pirzada, Umme Habiba (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Mini-CEX (Mini Clinical Evaluation Exercise) is extensively used in the west as a Workplace-based Assessment (WPBA) tool. However, its utility remains an infrequent in postgraduate medical training in Pakistan. Methods: Forty-eight mini-CEX sessions involving 11 faculty members and 15 postgraduate trainees were conducted over a 3‐month study period. Standardized American Board of Internal Medicine Mini‐CEX evaluation form was used to evaluate the students. The faculty and trainees were asked to provide feedback for these sessions on questionnaires consisting of close‐ and open‐ended questions. Results: Faculty satisfaction with mini-CEX was high, with all agreeing that it was an appropriate method of trainees’ assessment and teaching, and that it should be included in the curriculum. However, two-third of the faculty felt that it was not possible to assess students through mini-CEX more frequently. All trainees agreed that the sessions made them aware of their weaknesses and strengths. However, majority (73.3) complained that they were not given a chance to give reflection on their performance during the feedback session. Both residents and faculty suggested to incorporate Mini‐CEX in curriculum. Conclusion: It is feasible to use mini‐CEX for formative assessment of residents. Keywords: Workplace-based assessment, mini-clinical evaluation exercise, feedback